Chemobrain in patients suffering from cancer based on the example of multiple myeloma - Bury, Magdalena (Current Problems of Psychiatry, 2017)
Introduction: The incidence rate of cancers emphasizes the necessity to investigate not only patients’ somatic ailments but also their psychosocial functioning as well as the need to raise the quality standards of cancer patients. The improvement of the quality of life is one of the major challenges of psycho-oncology, which is the science created in the interface of two disciplines: psychology and medicine. One of the important aspects of psycho-oncologists’ activity is the minimization of negative side-effects related to treatment, such as changes in patients’ cognitive functioning resulting from anti-cancer treatment. Objective: The aim of this work is to provide the reader with the knowledge concerning the phenomenon of chemobrain in a very special group of patients with hematooncologic tumour. Few researches related to this topic have confirmed the occurrence of cognitive deficits resulting from the cancer process, taken cytotoxic drugs, other forms of anti-cancer therapy and the activeness of biochemical compounds in patients with multiple myeloma. Methods: The author has done a literary review concerning the topic under study using the Google Scholar and EBSCO databases. The main part of this work consists of references to Polish and English research literature published after 2000. The review includes also classic works from the eighties and nineties of the 20th century. Results: The present work has been divided into several sections. The part devoted to explanation of the term chemobrain describes the evolution of its definition over the years. The second section – ‘Heterogeneity of the phenomenon – causes’ – underlines the influence of biochemical etiological factors, such as the impact of the activity of proinflammatory cytokines on the cognitive state of the patients suffering from tumour. Next part – ‘Chemobrain and multiple myeloma’ is devoted to the clinical characteristics of this cancer and to the descriptions of the selected methods of chemotherapy. The review of researches concerning the deteriorated cognitive functioning of patients with multiple myeloma in relation to the probable aetiology of this disease has been also presented. Conclusions: The review of Polish and English literature concerning the functioning of memory and attention processes in the patients suffering from multiple myeloma can serve as an inspiration for a search for objective biochemical factors conditioning the dete-rioration of cognitive processes of the patients undergoing anti-cancer treatment.